Potential genotype-specific single nucleotide polymorphism interaction of common variation in p53 and its negative regulator mdm2 in cholangiocarcinoma susceptibility - ZIMMER, VINCENT (D.A. Spandidos, 2012)
Aberrant cell cycle control and apoptosis deregulation are involved in biliary carcinogenesis. The tumor suppressor gene p53 and its key negative regulator murine double minute 2 (mdm2) cooperate in modulating these basic cell functions and germline p53 alteration promotes cholangiocarcinoma (CCA) formation in animal models. The potential association between common functional genetic variation in p53 (SNP72 G/C) and mdm2 (SNP309 T/G) and susceptibility to bile duct cancer, however, has not been studied. p53/SNP72 G/C (rs1042522) and mdm2/SNP309 T/G (rs2279744) were genotyped in 182 Caucasian CCA patients and 350 controls using TaqMan assays. Allelic and genotypic differences, including exploratory data analyses (according to gender, tumor localization, early onset and genotypic interactions) were compared in contingency tables using the χ(2) and Fisher’s exact tests. The overall comparison of allele and genotype frequencies yielded no significant association between either SNP and CCA susceptibility. Similarly, gender- and localization-specific analyses did not reveal deviations in allelic or genotypic distributions. In carriers of the low-apoptotic p53 genotype CC, the mdm2 SNP309 T allele conferred borderline significant CCA risk [P=0.049; odds ratio (OR), 4.36; 95% CI, 0.92–20.77]. Power analysis confirmed adequate statistical power to exclude major SNP effects (each >97% for OR 1.7). Collectively, the results we obtained from the largest European CCA cohort do not support the hypothesis of a prominent role of common p53 and mdm2 variation in the genetic susceptibility to bile duct cancer. However, epistatic effects may modulate genetic CCA risk in individual subsets.